2022
DOI: 10.1039/d2gc01225a
|View full text |Cite
|
Sign up to set email alerts
|

Self-photocatalyzed regulable alkylation of 2H-benzothiazoles with diverse aliphatic C–H donors

Abstract: Visible light-driven self-catalyzed regulable alkylation of 2H-benzothiazoles with diverse aliphatic C–H donors via the combination of HAT and self-photoredox catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…We were pleased to find that substrates bearing chloro ( 5c ) and cyano ( 5d ) groups as well as a series of diol compounds ( 5e – 5h ) were all compatible with the reaction with their functional groups preserved, which further emphasized the potential of our system for synthetic applications. Interestingly, isopropanol and cyclohexanol led to a mixture of products ( 5i and 5i′, 5j and 5j′ ) in ratios of 4.2:1 and 8.3:1, respectively, by direct dehydrative coupling between heteroarenes and alcohols, which was consistent with our previous research …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were pleased to find that substrates bearing chloro ( 5c ) and cyano ( 5d ) groups as well as a series of diol compounds ( 5e – 5h ) were all compatible with the reaction with their functional groups preserved, which further emphasized the potential of our system for synthetic applications. Interestingly, isopropanol and cyclohexanol led to a mixture of products ( 5i and 5i′, 5j and 5j′ ) in ratios of 4.2:1 and 8.3:1, respectively, by direct dehydrative coupling between heteroarenes and alcohols, which was consistent with our previous research …”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, Li et al detailed the self-photocatalyzed methylation of diverse N -heteroaromatics using MeOH as the methylating agent. Very recently, our group disclosed self-photocatalyzed regulable alkylation of heteroarenes with diverse aliphatic C–H donors in which the heteroarene acted as a photocatalyst to induce the generation of chlorine radical, etc . Inspired by these initial results, we envisioned whether the photosensitivity of the heteroarenes could be applied to the multicomponent Minisci reaction to construct more complex molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5C, typical signals of DMPO‐•OOH are observed in the EPR spectra, and the intensity of activating O 2 is determined by the order of Co SAs‐N@C > Co NPs‐N@C ≈ N@C, hinting that the mechanism of oxidative esterification involves hydroxyl radical oxidation. It has been demonstrated that N‐species on carbon is capable of activating O 2 for aerobic oxidation, [ 4,13 ] oxygen reduction reaction, [ 37 ] and epoxidation reaction. [ 38 ] As expected, the oxidative esterification of FUR was significantly blocked by bubbling N 2 (Figure 4D) or adding butylated hydroxytoluene (BHT), a free‐radical scavenger (Figure 5D), further confirming that the oxidative esterification reaction proceeded as radical oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 3 g of the powdered mixture was annealed in a glass tube furnace under an argon atmosphere with a temperature program: from room temperature to 550°C at an elevated rate of 5°C/min, kept at 550°C for 2 h and then at 900°C for 4 h, and the flow rate of argon was set at 75 ml/min. [ 4,13 ] After cooling to room temperature, approximately 150 mg of the Co SAs‐N@C catalyst was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation